Planning of Solar Power Plants at Surya Market Regional Companies - Mochamad Iswahyudi; Trisna Wati (Procedia of Engineering and Life Science, 2021)
This Pasar Surya Surabaya Regional Company is an official market management under the Surabaya City government. In 2020, companies in the solar market area changed building assets into several open space places to become infrastructure facilities for economic improvement. The current power requirement is 197Kva and will be increased to 275 Kva. The planning of off-grid PV mini-grid for the Pasar Surya Regional Company, which was previously connected to PLN for 197 KVA, requires 1692 PV 380 WP for installation in an effective area of ​​3296.5 m2 and is divided into 3 PV arrays. with each array consisting of 19 series and 30 parallel PV arrays. Batteries with a capacity of 24V 300 Ah are needed as many as 342 pieces which are divided into 3 parts, with each part consisting of 19 series arrangement and 6 parallel battery arrangement. SCC (Solar Charge Controller) 240 KW requires as many as 3 pieces. Inverter 200 KW requires as much as 1 piece. In one year the energy that can be produced by PLTS is 950130 kWh, with a performance ratio showing the efficiency of PLTS at PD Pasar Surya which is 66.5%. The total cost of installing PLTS is around Rp. 16,204,258,086,- not including construction and installation costs. Meanwhile, to return the capital to be equivalent to the use of PLN, it takes an operating time of around 16 years